Influence of informal financial literacy training on financial knowledge and behavior of rural farmers: Evidence from Uganda - Proscovia, Ntakyo Renzaho; Johnny, Mugisha; Robert, Bangizi; Diana, Namwanje; Robert, Kalyebara (Journal of Development and Agricultural Economics, 2021)
Financial literacy plays an important role in influencing financial behavior and knowledge of individuals. In this study, the impact of informal financial literacy training on rural smallholder farmers was assessed. Propensity score matching approach was used to assess training effects on distinct dimensions of financial knowledge. The study used a sample of farmers who are members of village savings and loans associations. Findings indicate higher scores (70.6% for training beneficiaries and 68.5% for the control group) in financial goals and the lowest scores (48.0% for training beneficiaries and 43.0% for control group) in planning and managing finances. Although the descriptive statistics show higher scores for the trained farmers, overall financial literacy scores in the different dimensions for trained farmers were not significantly different from those that were not trained. The result was attributed to spillover effects through networks given the period between training and evaluation. More financial education programs could be useful to empower communities with knowledge for informed financial decision making.